Penerapan Pembelajaran Berbasis Proyek P5 Pada Pendidikan Anak Usia Dini - Padia Nadila Sari; Revilla Malik , Lina (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
One approach that is relevant to the needs of the times in early childhood is the implementation of Project Based Learning (PBL) which is integrated with the Strengthening Pancasila Student Profile (P5) program. At the Aisyiyah Bustanul Athfal 3 Samarinda Kindergarten, character strengthening through PBL is carried out by utilizing themes based on local wisdom and children's creativity. This research aims to examine the implementation of P5 project activities in PAUD. The research used a qualitative approach with a descriptive design, involving 18 children as subjects. Data was collected through participant observation, interviews with teachers and parents, as well as documentation of children's work, and analyzed descriptively. The research results show that project-based activities, such as making klepon and traditional games (congklak, pickles and marbles), as well as making wall decorations, have succeeded in improving children's social skills, including the ability to work together, communicate and tolerate. Apart from that, this activity enriches children's creativity in designing and making works of art, while introducing them to local cultural values. Children also demonstrate character strengthening in accordance with Pancasila values, such as mutual cooperation, responsibility and creativity. In conclusion, the implementation of project-based learning at ABA 3 Samarinda Kindergarten is effective in supporting early childhood development from various aspects, namely cognitive, social, emotional and cultural. This research suggests that PBL programs with themes based on local wisdom continue to be developed, and involve more participation from parents and the community to enrich children's learning experiences.